Peningkatan Hasil Belajar Statistik dengan Menggunakan Metode Pembelajaran Diskusi Terbimbing - Jainal Togatorop; Heryanto Heryanto (Universitas Quality, 2017)
This study aims to know increase in statistical learning outcomes used learning method discussion guided. Location of the study at the University Quality Medan. This type of research is in use in this research is a classroom action research that aims to improve student learning outcomes at the course Statistics.Researchers collected data by conducting tests to see student understanding of the material that has been studied. The Analyze of the data in this study is the student results of test data from the test results of each end of the cycle. Data student results obtained from tests conducted after the end of one cycle, were analyzed to see students learning completeness individually or get the value ≥B. In this study, expected results ≥B value may exceed 70% of the total number of studentsThe number of students who completed the first cycle of 27 students (67.5%) and who did not complete as many as 13 students (32.5%), while in the second cycle the number of students who pass the increase to 35 students (87.5%) and the number students who do not complete decreased to 5 students (12.5%). So it can be stated that by using the method of learning guided discussion on the subject of statistics completed both individually and in the classical style. The percentage of learning outcome of 29.9%.